2010
DOI: 10.4172/1948-5956.1000046
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect Between Curcumin (diferuloylmethane) and Radiation on Clonogenic Cell Death Independent of p53 in Prostate Cancer Cells

Abstract: Radiotherapy is a common treatment for prostate cancer, but failure is observed 30 to 40% of the time. It is more common in patients with abnormal p53. The phytochemical diferuloylmethane (curcumin) a naturally occurring fl avinoid derived from the rhizome of Curcuma longa, shows potential radiosensitizing effects. In the present study, the effect of curcumin and radiation on cell viability, apoptosis and clonogenic cell death was examined in LNCaP (wild type p53) and PC3 (mutant p53) prostate cancer cells.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Previous reports showed variable expression of p53 and/or mp53 in PC‐3 cells and mp53 upregulated 15‐lipoxygenase‐1 in murine and human PCA . In our study, we detected mp53 mRNA and protein expression in PC‐3 cells . Although the detailed functionality of mp53 protein in PC‐3 is unknown, the upregulation of mp53 by the XRT/RSV correlated with an antiproliferative effect on PC‐3 cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous reports showed variable expression of p53 and/or mp53 in PC‐3 cells and mp53 upregulated 15‐lipoxygenase‐1 in murine and human PCA . In our study, we detected mp53 mRNA and protein expression in PC‐3 cells . Although the detailed functionality of mp53 protein in PC‐3 is unknown, the upregulation of mp53 by the XRT/RSV correlated with an antiproliferative effect on PC‐3 cells.…”
Section: Discussionsupporting
confidence: 56%
“…Our data indicated that XRT/RSV disrupted the pro-proliferative mechanism and induced antiproliferative regulatory molecules in PC-3 to inhibit cell proliferation in treated cells. Previous reports showed variable expression of p53 and/or mp53 in PC-3 cells (40)(41)(42)(43)(44) and mp53 upregulated 15-lipoxygenase-1 in murine and human PCA. (43,45) In our study, we detected mp53 mRNA and protein expression in PC-3 cells.…”
Section: Discussionmentioning
confidence: 88%
“…Tumor-specific humoral immune responses directed against oncoproteins, mutated proteins such as p53 [69]. In many cancers humoral immune responses are induced by MUC 1.…”
Section: Humoral Immunitymentioning
confidence: 99%
“…Cell cycle and apoptosis was evaluated by flow cytometry. Cell viability and colony formation was examined using MTT assay and clonogenic assay respectively [48] the p53 mutations observed in tumors represent the expression of such instability by allowing the accumulation of genetic alterations caused by multiple mechanisms [49].…”
Section: Radiotherapymentioning
confidence: 99%